THE EXERCISE OF THE LINGUISTIC RIGHTS OF INDIGENOUS PEOPLES IN PERU: THE EXERCISE OF THE LINGUISTIC RIGHTS OF INDIGENOUS PEOPLES IN PERU - Huañahui Sillocca, Antonio Eliseo (2020)
This article deals with the linguistic rights of indigenous peoples in access to the administration of justice. Using indigenous languages individually and collectively is a right that the State has the obligation to recognize, respect, protect and promote. The original languages must be guaranteed, promoted and strengthened, however, in Peru the western culture still subordinates the indigenous peoples. This practice of domination is perceived as a “normal” fact that has been internalized in the indigenous population, generating a problem of self[1]esteem. It is necessary to build a new model of the State with multicultural and multilingual institutions and justice.